Twenty-six new species of Hoploscopa (Lepidoptera, Crambidae) from South-East Asia revealed by morphology and DNA barcoding - Théo Léger; Christian Kehlmaier; Charles S. Vairappan; Matthias Nuss (2020)
Hoploscopa Meyrick (Lepidoptera: Crambidae) is a fern-feeding genus found in montane areas of South-East Asia and Melanesia, eastwards up to the Samoan Islands. It includes sixteen described species, with at least 70 further undescribed species known from scientific collections. An iterative approach including morphological and molecular characters was used in order to explore the diversity of Hoploscopa. The hitherto described species are revised, and descriptions authored by T. Léger and M. Nuss are provided for an additional 26 new species: H. agtuuganonensis sp. nov., H. albipuncta sp. nov., H. albomaculata sp. nov., H. anacantha sp. nov., H. boleta sp. nov., H. cynodonta sp. nov., H. danaoensis sp. nov., H. gombongi sp. nov., H. gracilis sp. nov., H. ignitamaculae sp. nov., H. isarogensis sp. nov., H. jubata sp. nov., H. kelama sp. nov., H. kinabaluensis sp. nov., H. mallyi sp. nov., H. marijoweissae sp. nov., H. matheae sp. nov., H. niveofascia sp. nov., H. pangrangoensis sp. nov., H. parvimacula sp. nov., H. pseudometacrossa sp. nov., H. sepanggi sp. nov., H. sumatrensis sp. nov., H. titika sp. nov., H. tonsepi sp. nov., H. ypsilon sp. nov. Using a protocol specific for the amplification of DNA from old museum specimens, we recovered 101 COI barcodes for all but one of the newly described species, with 76 being barcode compliant (>487 bp). Species delimitation analyses suggest cryptic diversity, with six cases reflecting allopatric divergence, and two further cases found in sympatry.